EFFECTS OF PLANT GROWTH REGULATOR ON IN VITRO CALLOGENESIS OF GARDEN CRESS (LEPIDIUM SATIVUM L.) - SMRATI SHARMA; ANIL K. SINGH; RAVI P. SINGH; MUKESH K. SINGH; PRAKASH SINGH; C. MOHAPATRA (The Bioscan, 2015)
Three explants (seeds, shoot and root) of Garden cress (Lepidium sativum L.) were used for the standardization of previously reported protocol of callus initiation from seed and shoot explants under in-vitro conditions. The various combination of different concentration (0.0, 2.0, 4.0 and 6.0 mg/L) of plant growth regulators á- naphthalene acetic acid (NAA), 2, 4-Dichlorophenoxyacetic acid (2, 4-D) and Kinetin (Kin) were used in Murashige and Skoog (1962) medium (MS medium), to analyze the effect on explants of Garden cress for callus initiation. Plant growth regulators, 2, 4-D (4.0 and 6.0 mg/L) and Kin (2.0 mg/L) were found to be the most efficient combinations for calli formation (50 % and 20 % callus initiation from seeds and shoots inoculation, respectively). Globular and pale yellow callus was formed in the MS-medium containing 2, 4-D (4.00 to 6.00 mg/ L). Similar trends were also obtained for callus formation from shoot explants using MS-medium containing 2, 4- D (4.00 to 6.00 mg/L) and Kinetin (2.0 mg/L). However, higher concentrations of Kinetin i.e., more than 2.0 mg/ L did not show any improvement on callusing and also reduced the callus induction frequency from both explants. Highest amount/ number of callus formation (50 % callus initiation) were observed in culturing of seed in MS medium than the culturing of shoot and root explants. This study may be useful for rapid micropropagation or callus regeneration of Garden cress in in-vitro condition in future Lepidium improvement programme.